Laparoscopic Spleen-Preserving Distal Pancreatectomy Followed by Intramuscular Autologous Islet Transplantation for Traumatic Pancreatic Transection in a Young Adult - Dardenne, Sabrina; Sterkers, Adrien; Leroy, Christophe; Da Mata, Laurent; Zerbib, Philippe; Pruvot, François René; Pattou, François; Truant, Stéphanie (JOP. Journal of the Pancreas, 2012)
Context Pancreatic injuries caused by blunt trauma are often treated conservatively, except for the highest grades of these. Case report We report a case of complete transection of the distal pancreas in a young adult which was successfully managed by spleen-preserving laparoscopic distal pancreatectomy followed by an islet autotransplantation in the patient’s forearm striated muscle. Conclusion We describe a mini-invasive approach for pancreatectomy with restoration of resected islets to the patient.